P80 Sexual health in systemic lupus erythematosus: a cross-sectional analysis. (23rd March 2020) - Neto, Agna; Torres, Rita; Lopes, Carina; Mourão, Filipa; Branco, Jaime; Costa, Manuela
Abstract : Background/Purpose: Systemic Lupus Erythematosus (SLE) can affect different aspects of patients' life, including sexuality. Sexual dysfunction is an under-recognized multifaceted issue that may be caused by pain during intercourse, joint stiffness, functional limitations, fatigue or depression. This study aims to evaluate sexuality in SLE and to identify potential risk factors for sexual dissatisfaction. Methods: This is a cross-sectional observational study, which included patients diagnosed with SLE, aged between 18 and 65 years old. An anonymous patient-reported questionnaire was designed consisting of three domains: socio-demographic characteristics, disease characteristics and sexuality. The questionnaire was sent to all members of a national association of SLE patients. Mann-Whitney U test, Fisher's exact test or chi-square test were used to compare differences between groups, as appropriate. Results: A total of 215 patients were included, of which 84% were female. Mean age was 38.2 ± 10.4 years and mean disease duration was 13.2 ± 7.8 years. Nearly 82% were sexually active and had a mean frequency of sexual activities of 5.5 ± 2.5 per month. Among sexually active patients, 33% were sexually dissatisfied. There was no significant association between sexual satisfaction and age, gender, marital status, educational level, work status, use of walking aids, joint prosthesis or therapies used (table 1 ). Sexually dissatisfied patients had shorter disease duration (12.1 ± 6.2 vs 14.8 ± 9.1 years, p=0.036) and lower rates of remission (26.4% vs 45.8%) than those who were fully satisfied. The lower the disease activity, the higher the sexual satisfaction. Among sexually dissatisfied patients, 85% pointed out that SLE had a negative impact on their sexual health, while only 28% of sexually satisfied patients reported the same (p<0.001). Conclusion: Sexual dissatisfaction in patients with SLE is significantly associated with shorter disease duration and higher disease activity. Sexual health plays an essential role in these patients' quality of life and its assessment should be part of routine clinical care.